Content validation of a self-report daily diary in patients with sickle cell disease - Michelle K. White; Cory Saucier; Miranda Bailey; Denise D'Alessio; April Foster; Danielle St. Pierre; Kimberly Raymond (SpringerOpen, 2021)
Abstract Background Sickle Cell Disease (SCD) is a genetic progressive vascular disease that impacts patients overall health and quality of life. Sickle-cell pain crises (SCPCs) are a hallmark clinical presentation of SCD and have been associated with increased morbidity and mortality. The Sickle Cell Pain Diary- Self Report (SCPD-S) was developed as a daily patient-reported outcome (PRO) measure primarily intended to capture the frequency and severity of SCD-related pain during and outside of a SCPC. The SCPD-S also examines the impact of the pain associated with an SCPC on other health-related quality of life concepts. The objective of this study was to investigate the content validity of the SCPD-S. Methods The content validation testing included 18 in-depth hybrid concept elicitation and cognitive debriefing interviews conducted with SCD patients in the US aged 12 years and older. Interviewers used a semi-structured interview guide and a think-aloud approach for the cognitive debriefing portion. All interviews were recorded, transcribed, coded and analyzed. Results Eighteen interviews across two rounds were conducted. Round 1 hybrid interviews (n = 12) resulted in the expansion of the SCPD-S from 13 to 19 items. Items on the impact of an SCPC on social and recreational activities, sleep, and emotional well-being were added. Five items were significantly revised, as were three response choice sets. Round 2 hybrid interviews (n = 6) confirmed the comprehensiveness of the revised diary, understandability of the wording, and appropriateness of the recall period and response sets. Saturation analyses specific to concept elicitation revealed that no additional interviews were needed. Conclusions This study provided evidence to support the content validity of the SCPD-S, a self-report daily diary. Data gathered during patient interviews indicated that the SCPD-S is a fit for purpose measure of SCD and SCPC-related pain frequency and severity and the impact of this pain on other health-related quality of life concepts including fatigue and emotional health. The numerous changes to the SCPD-S as a result of the study findings highlight the importance of the content validation process when developing a PRO measure.